2020
DOI: 10.12659/msm.922424
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Long Non-Coding RNA X Inactive Specific Transcript (Xist) Contributes to Suppression of Bronchopulmonary Dysplasia Induced by Hyperoxia in Newborn Mice via microRNA-101-3p and the transforming growth factor-beta 1 (TGF-β1)/Smad3 Axis

Abstract: Background Bronchopulmonary dysplasia (BPD) is a chronic lung disease mostly affecting premature infants. Long non-coding RNA (lncRNA) X inactive specific transcript (Xist) is actively involved in pulmonary disease development. The present study explored the potential mechanism of Xist in BPD development. Material Methods First, newborn BPD mouse models were successfully established. lncRNAs and genes with differential expression were identified using microarray analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In addition, (36) found that SNHG6 can mediate lung cell damage by regulating the miR-335/KLF5/NF-κB pathway. The mechanism may be that Xist competitively binds miR-101-3p to activate HMGB3, and overexpression of miR-101-3p alleviates lung injury in BPD mice (37). lncRNA MALAT1 inhibits apoptosis and plays a protective role in BPD through the Keap1/Nrf2 signaling pathway (38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, (36) found that SNHG6 can mediate lung cell damage by regulating the miR-335/KLF5/NF-κB pathway. The mechanism may be that Xist competitively binds miR-101-3p to activate HMGB3, and overexpression of miR-101-3p alleviates lung injury in BPD mice (37). lncRNA MALAT1 inhibits apoptosis and plays a protective role in BPD through the Keap1/Nrf2 signaling pathway (38).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising because a variety of miRNAs are known to affect the BPD development in rodent models. In particular, it has been shown that miR‐421 negatively regulate the BPD development in hyperoxia‐insulted mice 22 ; whereas overexpression of miR‐101‐3p inhibits lung injuries in BPD mice 23 . In addition, both miR‐451 and miR‐203a‐3p actively participate in the BPD development in mice 24 and rats, 25 partially via regulating vascular growth and function increase.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that miR‐421 negatively regulate the BPD development in hyperoxia‐insulted mice 22 ; whereas overexpression of miR‐101‐3p inhibits lung injuries in BPD mice. 23 In addition, both miR‐451 and miR‐203a‐3p actively participate in the BPD development in mice 24 and rats, 25 partially via regulating vascular growth and function increase. We have previously revealed that miR‐185‐5p, which is lower in UCB‐EXO from BPD versus non‐BPD preterm pregnancies, promote endothelial angiogenesis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-acknowledged that lncRNAs can interact with microRNAs (miRNAs/miRs) to regulate downstream mRNA and gene expression ( 14 ). XIST targets miR-101-3p and inhibits its expression in silicosis, cancers, and bronchopulmonary dysplasia ( 15 - 18 ). Interestingly, miR-101-3p can repress vascular endothelial growth factor A (VEGFA) expression by targeting VEGFA mRNA, thus reducing cell migration and invasion ( 19 ).…”
Section: Introductionmentioning
confidence: 99%